A novel prosthetic finger design with high load-carrying capacity. (February 2021) - Liu, S.; Van, M.; Chen, Z.; Angeles, J.; Chen, C.
Highlights: A novel finger design is presented for use on 3D-printed hand prostheses. The finger can generate anthropomorphic motion comparable to that of a human finger. The finger is proven to have lower internal loads than existing prosthetic fingers. Load reduction is observed on prosthetic fingers featuring index to little sizes. The finger's improved load-carrying capacity has been verified in a destructive test. Abstract: Hand loss can cause a significant reduction in functionality and psychological damage, which can be partially recovered by hand prostheses. For 3D-printed prosthetic digits, internal joint forces are critical due to the low strength of 3D-printed components. This paper focuses on the analysis and verification of a novel five-link epicyclic (FLE) finger for 3D-printed hand prostheses. The motion and joint forces of the FLE design were analyzed and compared with the commonly-adopted coupled-four-bar linkage (CFBL) design. The results show that the FLE design yields a reduction in internal joint forces between 21.32% and 86.52%, and mimics the proportions and anthropomorphic motion of a human digit. A destructive test was conducted, which experimentally demonstrated the increased load-carrying capacity of the FLE finger. Therefore, the functionality of a hand prosthesis carrying a FLE finger is expected to be improved over that with a CFBL finger, and thus benefit patients suffering hand loss.